ALIH EDUKASI MELALUI VISUALISASI MURAL DI TK HEMAN BANDUNG - Ariesa Pandanwangi; Belinda Sukapura Dewi; Ismet Zainal Effendi Zainal Effendi; Wawan Suryana; Muhamad Ali Rahim; Erika Ernawan; Basituasi Baene (Jurnal Abdimas Bina Bangsa, 2024)
Play while learning, widely implemented into the creative educational process in kindergarten schools. One of them is at Heman Christian Kindergarten located on Jl. Pajajaran no 91 Bandung. This school seeks to utilize the content of education through empty walls that have not been utilized so far. The use of this wall is expected to be a transfer of knowledge for students aged 4-6 years about the diversity of flora and fauna in Indonesia. Partners have problems to be able to change the existing environment into a colorful environment according to the age of the child, able to educate as well as change the environment to be tidier and radiate spirit energy through the colors that appear. To solve this problem, the solution was made a strategy by making a mural with a size of 2.44 m2 x 10 wall plane = 20.44 m2. Participatory methods are used in this devotion. PkM participants who will take part in the assistance in making this mural are 17 people. The result of this dedication mural is made in the primary colors red yellow green blue blue, the visualized objects are dominated by flora objects that represent flora from the archipelago